1980
DOI: 10.1080/17450398009425649
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Anämie bei männlichen Aufzuchtkälbern

Abstract: With 195 male rearing calves which received concentrates ad libitum beside fluid feed with milk from their 5th day of life onward, investigations were made if and how far the characteristics of the development of the calves while they are fed on colostrum (body weight at birth, live weight increase and duration of keeping or stalling age) correlate with the hemoglobin content (Hb), the hematocrit (Hc) and the average corpuscular hemoglobin concentration (MCHC) of the animals on the 3rd, 28th resp. 56th day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Iron is one of the important factors that influence growth, productivity, and animal immunity [ 9 ]. By feeding only cow’s milk to young ruminant calves, iron intake is insufficient for normal erythropoiesis during the first month of life [ 8 ], which is manifested by reduced blood parameters, such as red blood cell (RBC), hematocrit (HCT) and hemoglobin (HGB) [ 20 ]. Volker and Rotermund [ 7 ] reported that oral administration of 100 mg iron per day, prevented anemia in calves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron is one of the important factors that influence growth, productivity, and animal immunity [ 9 ]. By feeding only cow’s milk to young ruminant calves, iron intake is insufficient for normal erythropoiesis during the first month of life [ 8 ], which is manifested by reduced blood parameters, such as red blood cell (RBC), hematocrit (HCT) and hemoglobin (HGB) [ 20 ]. Volker and Rotermund [ 7 ] reported that oral administration of 100 mg iron per day, prevented anemia in calves.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Fe in the blood of young calves can vary by a wide range, from less than 10 μmol/L to as high as 30 μmol/L [ 2 , 25 ]. Moreover, over the first few days of life a progressive reduction in serum Fe concentration occurs, thus many authors point to the need for supplementation [ 2 , 20 ]. Primary iron deficiency is associated with a decrease of this trace element concentration in blood serum and elevated total iron binding capacity (TIBC) and unsaturated iron binding capacity (UIBC) [ 6 ].…”
Section: Resultsmentioning
confidence: 99%